Where and with whom do you wanna meet?: Session-based collaborative work - Arantes, Flávia Linhalis; Moraes, Claudia Roberta de; Silva, Salomão Henrique Pereira; Fortes, Renata Pontin M.; Pimentel, Maria da Graça C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2010: Proceedings of the 16th Brazilian Symposium on Multimedia and the Web, 2010)
In this paper we revisit the concept of session applied to collaborative work and define a set of operators to manipulate session information related to workspaces and tools scheduling in collaborative environments. By means of a proof-of-concept implementation which uses web services and context-aware tools, we show an example of how session information provided by the operators can be used to leverage the ubiquitous capabilities of collaborative applications.